MEMPERKUAT PERAN MAHASISWA DALAM MENYEBARKAN MODERASI DI MEDIA SOSIAL - Wijayanti, Tri Yuliana; Harlis, Syukri Alfauzi (JURNAL AL-AQIDAH, 2023)
Along with the progress of increasingly sophisticated technological developments in the current era, social media occupies an important and vital position in conveying information to the wider community in all circles. Social media seems to have become an addiction in this era, especially for students. The openness of the younger generation, especially students, to various information on social media makes them occupy a strategic position in efforts to spread religious moderation. Using descriptive analysis research methods, researchers analyze and identify what strategies are appropriate and suitable for increasing and strengthening the role of students in spreading moderation on social media. Based on the research results, the author found that students need to receive training in analyzing hoaxes, strengthening peace building campaigns and increasing capacity.